Mediated Communication - Napoli, Philip M. (Handbooks of communication science ;, 2018)
"Media scholarship has responded to a rapidly evolving media environment that has challenged existing theories and methods while also giving rise to new theoretical and methodological approaches. This volume explores the state of contemporary media research. Focusing on intellectual foundations, theoretical perspectives, methodological approaches, context, and contemporary issues, this volume is a valuable resource for media scholars and students"--